Peran Pedagogik dan Kompetensi Spiritual Guru PAK dalam Peningkatan Spiritualitas Naradidik - Paembonan, Y. M. (Sekolah Tinggi Teologi Kanaan Nusantara, 2022)
This study contains a discussion of how the pedagogic role and spiritual competence of Christian religious education teachers have in improving the spiritual competence of students. Spiritual competence is an absolute requirement that must be possessed by students in facing the challenges of today's world which are increasingly threatening. Facts on the ground prove that there are many Christian religious education teachers who teach solely because they do work to make a living without realizing the great and noble responsibility behind their profession. As a result, students do not get spiritual exemplary and spiritual aspects within themselves. Christian religious education teachers are given the responsibility to form students who are in accordance with the character of Jesus, so that Christian religious education teachers should provide teaching and examples that can be imitated by students in developing the spiritual values that the Lord Jesus has given. Christian religious education teachers themselves must first master good pedagogic and spiritual competencies so that what is taught can really be embedded in the hearts and minds of students. This study uses qualitative methods through literature studies that are in accordance with the variables studied. The results of this study are in the form of a description that concludes the correlation between these variables. From this research, it can be concluded that Christian religious education teachers can improve the spiritual of students if Christian religious education teachers are able to improve pedagogic competence and spiritual competence that can be emulated from a Christian religious education teacher.AbstrakPenelitian ini berisi pembahasan mengenai bagaimana peranan pedagogik dan kompetensi spiritual yang dimiliki guru pendidikan agama Kristen dalam meningkatkan kompetensi spiritual dari naradidik. Kompetensi spiritual merupakan syarat mutlak yang harus dimiliki oleh naradidik dalam menghadapi tantangan dunia saat ini yang semakin mengancam. Fakta di lapangan membuktikan banyaknya guru PAK yang mengajar hanya semata karena menjalankan pekerjaan mencari nafkah tanpa menyadari tanggung jawab besar dan mulia dibalik profesi yang disandangnya. Akibatnya peserta didik tidak memperoleh keteladanan spiritual dan aspek spiritual dalam dirinya. Guru PAK diberikan tanggungjawab untuk membentuk naradidik yang seturut dengan karakter Yesus, sehingga sudah sepatutnya guru PAK memberikan pengajaran dan teladan yang mampu ditirukan oleh naradidik dalam menumbuhkembangkan nilai-nilai spiritualitas yang telah Tuhan Yesus berikan. Guru PAK sendiri haruslah menguasai kompetensi pedagogik dan kompetensi spiritual yang baik terlebih dahulu sehingga apa yang diajarkan dapat benar-benar tertanam dalam hati dan pikiran naradidik. Penelitian ini menggunakan metode kualitatif melalui studi literatur yang sesuai dengan variable yang diteliti. Hasil dari penelitian ini berupa deskripsi yang menyimpulkan korelasi antara variable tersebut. Dari penelitian tersebut dapat disimpulkan bahwa guru PAK dapat meningkatkan spiritual naradidik apabila guru PAK mampu meningkatkan kompetensi pedagogik dan kompetensi spiritual yang dapat diteladani dari seorang guru PAK.